Electromagnetic Shielding Analysis (EMS) of Hybrid Multilayered Woven Fabric at Different Transmitter Distance - K. Omar, N.; F. Yahya, M.; R. Ahmad, M.; T. Ali, M. (International Journal of Engineering and Technology, 2019)
This paper mainly discusses on the effectiveness of multiple plain-woven fabric towards electromagnetic shielding (EMS). The measurement includes the effect of fabric distance from the transmitter antennas in the shielded enclosure test. The conductive fabric consists of copper cover hybrid yarns produced using hollow spindle spinning machine. The electromagnetic shielding test was performed according to IEEE-299 specification at 2000MHz. The range was selected to reflect mobile phones, wireless fidelity, Bluetooth and GPS transmission range frequencies.  Four samples of conductive fabrics were used in the work, as 0°/0°, 90°/90°, 0°/90° and 90°/0, respectively. The fabric sample with 0°/90° alignment was found to give the best electromagnetic shielding at -65.79dBM. The initial results also show that the hybrid conductive fabrics have large potential to be utilized for shielding electromagnetic radiation (EMR).